Association Between Precautionary Behaviors and Breast Cancer–Related Lymphedema in Patients Undergoing Bilateral Surgery - Maria S. Asdourian; Meyha N. Swaroop; Hoda E. Sayegh; Cheryl L. Brunelle; Amir I. Mina; Hui Zheng; Melissa N. Skolny; Alphonse G. Taghian (Journal of Clinical Oncology, 2017)
Purpose This study examined the lifestyle and clinical risk factors for lymphedema in a cohort of patients who underwent bilateral breast cancer surgery. Patients and Methods Between 2013 and 2016, 327 patients who underwent bilateral breast cancer surgery were prospectively screened for arm lymphedema as quantified by the weight-adjusted volume change (WAC) formula. Arm perometry and subjective data were collected preoperatively and at regular intervals postoperatively. At the time of each measurement, patients completed a risk assessment survey that reported the number of blood draws, injections, blood pressure readings, trauma to the at-risk arm, and number of flights since the previous measurement. Generalized estimating equations were applied to ascertain the association among arm volume changes, clinical factors, and risk exposures. Results The cohort comprised 327 patients and 654 at-risk arms, with a median postoperative follow-up that ranged from 6.1 to 68.2 months. Of the 654 arms, 83 developed lymphedema, defined as a WAC ≥ 10% relative to baseline. On multivariable analysis, none of the lifestyle risk factors examined through the risk assessment survey were significantly associated with increased WAC. Multivariable analysis demonstrated that having a body mass index ≥ 25 kg/m 2 at the time of breast cancer diagnosis ( P = .0404), having undergone axillary lymph node dissection ( P = .0464), and receipt of adjuvant chemotherapy ( P = .0161) were significantly associated with increased arm volume. Conclusion Blood pressure readings, blood draws, injections, and number or duration of flights were not significantly associated with increases in arm volume in this cohort. These findings may help to guide patient education about lymphedema risk reduction strategies for those who undergo bilateral breast cancer surgery.